HOW TO PROTECT BOTANICAL DIVERSITY IN CENTRAL ASIA FROM DESTRUCTION AND PROMOTE ITS RESTORATION: PRIORITIES AND MAINSTREAMING APPROACHES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article proposes for discussion by the professional botanical community and all interested parties measures for the conservation and restoration of botanical diversity of Central Asia.
Keywords: ex situ and in situ conservation, restoration ecology, citizen science, ecosystem approach, econet, GBIF.